Association between Serum Alkaline Phosphatase and Nocturia: A Cross-Sectional Study in a Diabetic Population - He, Liqian; Wang, Xudong; Li, Zeseng; Shi, Jian (Journal of Contemporary Medical Practice, 2025)
Nocturia in the diabetic population is a serious public health condition that is becoming increasingly common worldwide. Limited data on the association of alkaline phosphatase (ALP) with Nocturia warrants further attention. We analyzed data using the National Health and Nutrition Examination Survey (NHANES) from 2009-2018. Indicators related to ALP, Nocturia, Diabetes mellitus, and related covariates were extracted and analyzed. Logistic regression models were used to explore the independent correlation between serum ALP and Nocturia. We then assessed whether there was a non-linear relationship between the two using Restricted Cubic Splines (RCS) and performed subgroup analyses. The study population comprised 4479 diabetic patients (2353 males and 2126 females) aged 20 years or older. The prevalence of nocturia in the diabetic population was 49.2% (2202/4479). Multifactorial logistic regression analysis shows positive association between ALP and nocturia. Interaction tests demonstrated that the positive association between ALP and Nocturia interacted with age (interaction p < 0.05). Based on a representative sample of the US diabetic population, we found that higher levels of ALP were significantly associated with the risk of nocturia, even when ALP levels were within the normal range. This finding requires further prospective studies to provide additional evidence.